Ecovilas: uma análise comparativa a partir das dimensões da sustentabilidade - Fabri, Adriano (2015)
The dissertation project is focused on sustainability, an issue that is increasingly evident due to the environmental crisis in contemporary society. Analyze the level of development of practices related to the dimensions of sustainability (ecological, social, economic and cultural) present in the ecovillage is your main goal. The research is exploratory uses literature method for the theoretical context and the empirical support makes use of data sample survey by applying online questionnaire to representatives of (50) fifty ecovillages from Latin America, which resulted in (9) nine effective responses, of which were selected two (2) ecovillages to carry out the field trip. Visa to the investigation of how the residents of the ecovillage relate to each other, with nature and which technologies they use. Among the results, we emphasize the mapping of the main practices, and the development level of these according to the perception of the respondents and observation performed in the field. Finally, we highlight that the results found in the research may help in the improvement of existing communities and planning new initiatives.